2009
DOI: 10.2332/allergolint.o-07-526
|View full text |Cite
|
Sign up to set email alerts
|

Sho-seiryu-to Suppresses Histamine Signaling at the Transcriptional Level in TDI-Sensitized Nasal Allergy Model Rats

Abstract: These results demonstrate that SST alleviates nasal symptoms by the inhibition of histamine signaling through suppression of TDI-induced H1R and HDC gene up-regulation. SST also suppresses cytokine signaling through suppression of IL-4 and IL-5 gene expression. Suppression of histamine signaling may be a novel mechanism of SST in preventing allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Additionally, TDI-sensitized rats also display many of the characteristic features of AR in humans, including infiltration of eosinophils and mast cells (40), increase in the level of cytokines (8,(41)(42)(43), elevation of H1R mRNA and protein level (12), increase in the HDC mRNA level, HDC activity, and histamine content (13), even though histamine release was triggered by neuropeptide, but not IgE, in TDI-sensitized animals. Furthermore, the expression of IL-4 and IL-5 mRNAs was also up-regulated in the nasal mucosa of TDI-sensitized rats after provocation with TDI (16,17). Therefore, we consider that TDI-sensitized rats can be a model of AR.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, TDI-sensitized rats also display many of the characteristic features of AR in humans, including infiltration of eosinophils and mast cells (40), increase in the level of cytokines (8,(41)(42)(43), elevation of H1R mRNA and protein level (12), increase in the HDC mRNA level, HDC activity, and histamine content (13), even though histamine release was triggered by neuropeptide, but not IgE, in TDI-sensitized animals. Furthermore, the expression of IL-4 and IL-5 mRNAs was also up-regulated in the nasal mucosa of TDI-sensitized rats after provocation with TDI (16,17). Therefore, we consider that TDI-sensitized rats can be a model of AR.…”
Section: Discussionmentioning
confidence: 95%
“…Among them, IL-4 plays a central role in allergic inflammation: it is associated with the development of T lymphocytes, acts as a growth factor for Th2 cells, stimulates IgE synthesis, and is involved in mast cell activation (15). Previous reports that the expression of IL-4 and IL-5 mRNAs was up-regulated in nasal mucosa suggest the involvement of these cytokines in nasal hyperresponsiveness in TDI-sensitized rats (16,17).…”
Section: A Llergic Rhinitis (Ar)mentioning
confidence: 99%
“…The H1R expression level is highly correlated to the severity of allergic symptoms, and compounds that suppress H1R gene expression alleviate allergic symptoms (12)(13)(14)(15)(16). Therefore, drugs targeting the proteins that compose the signaling pathway involved in histamine-induced up-regulation of H1R gene expression could be good therapeutics for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 91%
“…Furthermore, there are several in vivo reports concerning SST immunomoduratory action on allergic pathology, such as suppression of Th2 differentiation at the level ofsynapse between antigenpresenting cells and CD4+ T cells (7), inhibition of histamine signaling targeting its receptor expression and synthesizing enzyme (8), and augmentation of NGF induction accompanied by allergic pathology.…”
Section: Discussionmentioning
confidence: 99%